Epigenetic regulation of macrophage polarization and inflammation by DNA methylation in obesity - Xianfeng Wang; Qiang Cao; Liqing Yu; Huidong Shi; Bingzhong Xue; Hang Shi (JCI Insight, 2016)
Obesity is associated with increased classically activated M1 adipose tissue macrophages (ATMs) and decreased alternatively activated M2 ATMs, both of which contribute to obesity-induced inflammation and insulin resistance. However, the underlying mechanism remains unclear. We find that inhibiting DNA methylation pharmacologically using 5-aza-2′-deoxycytidine or genetically by DNA methyltransferase 1 (DNMT1) deletion promotes alternative activation and suppresses inflammation in macrophages. Consistently, mice with myeloid DNMT1 deficiency exhibit enhanced macrophage alternative activation, suppressed macrophage inflammation, and are protected from obesity-induced inflammation and insulin resistance. The promoter and 5′-untranslated region of peroxisome proliferator-activated receptor γ1 (PPARγ1) are enriched with CpGs and are epigenetically regulated. The saturated fatty acids stearate and palmitate and the inflammatory cytokine TNF-α significantly increase, whereas the TH2 cytokine IL-4 significantly decreases PPARγ1 promoter DNA methylation. Accordingly, inhibiting PPARγ1 promoter DNA methylation pharmacologically using 5-aza-2′-deoxycytidine or genetically by DNMT1 deletion promotes macrophage alternative activation. Our data therefore establish DNA hypermethylation at the PPARγ1 promoter induced by obesity-related factors as a critical determinant of ATM proinflammatory activation and inflammation, which contributes to insulin resistance in obesity.